Informal Employment in Russia: Incidence, Determinants and Labor Market Segmentation - Hartmut Lehmann; Anzelika Zaiceva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper takes stock of informal employment in Russia analyzing its incidence and determinants. Using the regular waves and an informality supplement of the Russian Longitudinal Monitoring Survey (RLMS) it develops several measures of informal employment and demonstrates that the incidence varies widely across the different definitions. We also show that the determinants of informal employment are roughly stable across the different measures: workers who are males, relatively young, unskilled and employed in construction and trade and related services have a higher likelihood to have an informal job. We also take a look at the issue of labor market segmentation along the informal-formal divide by estimating an informal-formal wage gap at the means and across the entire wage distributions. We find only weak evidence for labor market segmentation in Russia when estimating an informal-formal wage gap for salaried workers at the mean. The results of quantile regressions show a wage penalty in the lower half of the distribution and no gap in the upper half for informal employees. In contrast, informal self-employed and entrepreneurs have conditional mean wages that are higher than the mean wages for the formally employed. Across the entire wage distribution, however, we find a negative wage gap in the lowest quartile and a strongly positive wage gap in the highest quartile, pointing to a segmented informal sector with a lower free entry tier and an upper rationed tier.
Keywords: J31; J40; P23; 330